Checkmate: Exploring Backward Induction among Chess Players - Levitt, Steven D; List, John A; Sadoff, Sally E (American Economic Review, 2011)
Although backward induction is a cornerstone of game theory, most laboratory experiments have found that agents are not able to successfully backward induct. We analyze the play of world-class chess players in the centipede game, which is ill-suited for testing backward induction, and in pure backward induction games—Race to 100 games. We find that chess players almost never play the backward induction equilibrium in the centipede game, but many properly backward induct in the Race to 100 games. We find no systematic within-subject relationship between choices in the centipede game and performance in pure backward induction games. (JEL C73)